2021
DOI: 10.1039/d0ra10688g
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of porphyrins in fossil plants and animals

Abstract: Porphyrin derivatives such as heme, which is present in blood, and chlorophylls found in plants and bacteria, are complexes of high chemical stability which can survive hundreds of millions of years. Examples from the fossil record are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Recent studies found that iridophores in the dermis of a gecko can produce greenish UV-PL (Prötzel et al 2021). The reddish UV-PL observed on the plumage of some birds was identi ed as caused by coproporphyrin III and protoporphyrin IX (Church & Oxon 1869;Rimington 1938;Negro et al 2009;Okazaki & Imamura 2019;Camacho et al 2019;Galván et al 2016), which are common molecules that play a crucial role in various biological processes, notably in heme biosynthesis (Ajioka, Phillips & Kushner 2006;Tahoun et al 2021). Recent analyses of the hair of springhares (Pedetes sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that iridophores in the dermis of a gecko can produce greenish UV-PL (Prötzel et al 2021). The reddish UV-PL observed on the plumage of some birds was identi ed as caused by coproporphyrin III and protoporphyrin IX (Church & Oxon 1869;Rimington 1938;Negro et al 2009;Okazaki & Imamura 2019;Camacho et al 2019;Galván et al 2016), which are common molecules that play a crucial role in various biological processes, notably in heme biosynthesis (Ajioka, Phillips & Kushner 2006;Tahoun et al 2021). Recent analyses of the hair of springhares (Pedetes sp.)…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been used for the study of porphyrins, such as high-performance liquid chromatography (HPLC) [ 9 , 10 , 11 , 12 , 13 ], capillary electrophoresis (CE) [ 14 ], spectrofluorometry [ 15 ], laser desorption/ionization time of flight mass spectrometry (LDI-TOF–MS) [ 16 ] and fast atom bombardment mass spectrometry (FAB-MS) [ 17 ]. HPLC is currently established as the standard technique for the quantitative analysis of porphyrins for the diagnosis of human porphyrias [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of metal chelation with chemical agents involves the use of suitable chemical agents characterized by a higher complexation tendency towards vanadium and nickel, followed by the possible release from the porphyrin framework [50][51]. A study by Mokhtari and Pourabdollah [52] showed the vanadylporphyrin extraction process, using calix [4]arene, a nano-basket dicarboxylic acid.…”
Section: ■ Removal Of Metallic Porphyrins From Crude Oilsmentioning
confidence: 99%